DEKONSTRUKSI MITOS GENDER MELALUI ANALISIS KESETARAAN CAPAIAN NILAI UTS DI SEKOLAH DASAR - Aqina Hawa Maharani SW (Elementary School and Education Journal, 2026)
Society generally believes that males always have superior abilities in mathematics than females. This study aims to test this gender theory through a comparative analysis of the Mathematics Mid-Term Exam scores of 4th and 5th grade students in elementary school. This quantitative study involved 51 students divided into 2 groups of educational levels. The obtained Mid-Term Exam data were then processed using the Independent Sample T-Test and Mann-Whitney U with the help of SPSS software. The results of the data analysis showed that in grades 4 and 5 there was no significant difference in Mathematics Mid-Term Exam scores between genders with Sig. values ​​of 0.085 and 0.525. This finding reaffirms that there is no difference in students' mathematical cognitive abilities caused by gender differences. This study has broken many existing stereotype theories and promoted a more inclusive education system. This study also shows that students at the elementary school level can have an incremental perspective to maintain equal achievement at the educational level.